Enhancing Sustainability in the Injection Moulding Process via Reprocessing of Polypropylene Nanoclay Nanocomposites - Nadzi, Muhammad Fakhrullah; Ir. Ts. Dr. Mohd Hilmi Bin Othman (Research Progress in Mechanical and Manufacturing Engineering, 2026)
A study investigating the impact of reprocessing cycles on the hardness and impact strength of polypropylene-nanoclay nanocomposites (PPNC) has been conducted. The PPNC was composed of 80wt. % TITANPRO SM240 polypropylene (PP), 15wt. % Orevac CA100 maleic anhydride grafted polypropylene, and 5wt. % Cloisite 15A nanoclay. The research commenced by conducting an injection molding technique on PPNC. The generated samples were assessed based on their impact strength and hardness. Subsequently, the materials were pulverized into pellets in order to undergo additional reprocessing cycles. The reprocessing procedure was iterated four times. The hardness and impact strength were measured using the Shore hardness test and Tensile testing method, respectively. For the purpose of comparison, pristine polypropylene (PP) also underwent the identical reprocessing procedure as PPNC. According to this study, it was shown that when the reprocessing cycle of PPNC grew, there was a drop in both the hardness number and impact strength of PPNC. The hardness of PPNC reduced by a total of 6.56% from the first reprocessing cycle to the fourth reprocessing cycle. However, the impact strength of PPNC decreased from the second reprocessing cycle to the fourth reprocessing cycle. The whole decline amounted to 14.29%. The reprocessing cycle has had a greater impact on the impact strength of PPNC compared to its effect on the hardness of PPNC. However, in comparison to PPNC, plain PP exhibits superior hardness and impact strength. Thus, PP proved to be a superior choice for reprocessing material in comparison to PPNC.